Instruction And Assessment For Vocabulary Development In Bright: An English Course Seventh Graders - Gracella Panjaitan; Fiber Yun A Ginting; Sejahtra; Asta Br. Sembiring; Fori Pandiangan; Futri Sidabutar (Journal of Classroom Action Research, 2026)
This study examines the efficacy of "Bright: An English Course for SMP/MTs Grade VII" in Indonesia's Kurikulum Merdeka. The research uses a descriptive qualitative document analysis to evaluate vocabulary growth, presentation, and evaluation for seventh-grade students. The analytical approach makes use of Alan Cunningsworth's checklist and a cognitive audit based on the Revised Bloom's Taxonomy. The findings show strong curricular alignment (90.62%) and methodological quality (94.57%). However, there is a considerable cognitive imbalance, with 81% of tasks focusing on Lower Order Thinking Skills (LOTS), particularly in the "Remembering" (48%) and "Understanding" (33%) categories. Cultural representation research demonstrates a strong preference for Indonesian source culture (72.48%) over target (4.79%) and worldwide cultures (22.73%). Pedagogical implications suggest that, while the textbook is an excellent foundational tool, educators should supplement it with Higher Order Thinking Skill (HOTS) activities and more diverse intercultural content to promote global communicative agency. This guarantees that students acquire both the linguistic proficiency and critical cultural understanding required for 21st-century global citizenship. Keywords: Bright Textbook, Vocabulary Instruction, Kurikulum Merdeka, EFL, Bloom's Taxonomy.